2010
DOI: 10.1038/cdd.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Granzymes in age-related cardiovascular and pulmonary diseases

Abstract: Chronic inflammation is a hallmark of age-related cardiovascular and pulmonary diseases. Granzymes are a family of serine proteases that have been traditionally viewed as initiators of immune-mediated cell death. However, recent findings suggest that the pathophysiological role of granzymes is complex. Emerging functions for granzymes in extracellular matrix degradation, autoimmunity, and inflammation suggests a multifactorial mechanism by which these enzymes are capable of mediating tissue damage. Recent disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 84 publications
0
68
0
Order By: Relevance
“…34,35 Interestingly, it is also known that GzmB-mediated cleavage of IL-1a can occur extracellularly by GzmB derived from NK cells, 35 further highlighting the potential importance of perforin-independent GzmB activity in health and disease. In fact, both cytotoxic and non-cytotoxic activities of GzmB are suggested to have a role in many inflammatory disorders such as diabetes, cancer, transplant rejection, autoimmunity, cardiovascular and pulmonary diseases (reviewed in refs [36][37][38][39][40] ). Although its role in wound healing has never been assessed, considerable evidence exists that would support a role for GzmB in chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Interestingly, it is also known that GzmB-mediated cleavage of IL-1a can occur extracellularly by GzmB derived from NK cells, 35 further highlighting the potential importance of perforin-independent GzmB activity in health and disease. In fact, both cytotoxic and non-cytotoxic activities of GzmB are suggested to have a role in many inflammatory disorders such as diabetes, cancer, transplant rejection, autoimmunity, cardiovascular and pulmonary diseases (reviewed in refs [36][37][38][39][40] ). Although its role in wound healing has never been assessed, considerable evidence exists that would support a role for GzmB in chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, novel extracellular and perforin-independent functions have been identified (24,25). It has been demonstrated that Gr-mediated extracellular matrix (ECM) degradation may contribute to inflammation (26)(27)(28)(29)(30). GrB degrades several ECM components, such as vitronectin, laminin, fibronectin, decorin, and the proteoglycans biglycan and betaglycan (31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Although there are certainly more questions than answers at this time, many of these ideas are beginning to be addressed. As discussed in-depth in the review by Hendel et al, 13 emerging studies are beginning to demonstrate a potential perforin-independent, extracellular role for granzymes in disease.…”
mentioning
confidence: 99%